Menjaga Garis Tipis : Etika Profesi Akuntan Publik dalam Persimpangan Kepentingan (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the implementation of professional ethics among public accountants in Indonesia, particularly when facing conflicts of interest. Using a qualitative descriptive approach and secondary data analysis from published cases, audit reports, and academic literature, the research identifies patterns and contributing factors to ethical violations. The findings show that most violations stem from compromised independence, external pressure from clients, and weak enforcement of professional standards. Despite existing ethical guidelines issued by professional bodies and regulators, public accountants still face challenges in upholding integrity when their professional responsibilities intersect with financial or relational interests. The study emphasizes the need for stronger supervision, continuous ethical training, and a more proactive role from professional organizations in promoting ethical conduct. This research contributes to a deeper understanding of ethical dilemmas in the public accounting profession and provides insights for improving ethical practices and oversight mechanisms in Indonesia.